Preventing and preparing for disaster displacement - Essig, B; Moretti, S; Platform on Disaster Displacement Secretariat (Refugee Studies Centre, University of Oxford, 2020)
Examples of good practice relating to preventing, mitigating and preparing for disaster displacement, discussed as part of the GP20 initiative, have revealed valuable lessons on early action, data, laws and policies, and community engagement.